1988
DOI: 10.1099/00221287-134-1-169
|View full text |Cite
|
Sign up to set email alerts
|

Plant and Bacterial Chitinases Differ in Antifungal Activity

Abstract: Chitinases were isolated from the grains of wheat, barley and maize, and compared with those obtained from Serratia marcescens, Streptomyces griseus and Pseudomonas stutzeri for antifungal activity and enzyme specificity. The six enzymes were tested for antifungal activity using an assay based upon inhibition of hyphal extension of the fungi Trichoderma reesei and Phycomyces blakesleeanus. Antifungal activity was observed with as little as 1 pg of each of the grain chitinases, whereas none of the bacterial chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
268
0
8

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(282 citation statements)
references
References 15 publications
3
268
0
8
Order By: Relevance
“…6) like the plant chitinases. 8,[16][17][18][19][20] Thus, the antifungal activity appears to be a general property of the family 19 chitinases. Iseli et al 20) reported that a deletion of the ChBD (ChBDTob) from a tobacco class I chitinase results in about a 3-fold reduction of antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) like the plant chitinases. 8,[16][17][18][19][20] Thus, the antifungal activity appears to be a general property of the family 19 chitinases. Iseli et al 20) reported that a deletion of the ChBD (ChBDTob) from a tobacco class I chitinase results in about a 3-fold reduction of antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…8,[16][17][18][19][20] Class I and IV enzymes of plant family 19 chitinases have a cysteine-rich chitin-binding domain (also referred to as the hevein domain or the wheat germ agglutinin domain) at their N-termini. This domain increases the antifungal function of the catalytic domain.…”
mentioning
confidence: 99%
“…In experiments comparing different carbon sources for chitinase production, glucose, colloidal chitin, and fungal cell wall preparations were tested at the same concentration. Colloidal chitin was prepared from crude chitin by the method of Roberts and Selitrennikoff (25). Cell walls of B. sorokiniana and Pythium ultimum were extracted from 7-day-old broth cultures in a minimal medium according to the procedure of Sivan and Chet (27).…”
Section: Methodsmentioning
confidence: 99%
“…Chitinase activity was inhibited by Hg 2+ and Fe 3+ , but not by other metal ions or enzyme inhibitors. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of the chromatography fraction revealed the presence of five protein bands of 25,32,48,65, and 75 kDa. Partial amino acid sequences of the 32-, 65-, and 75-kDa proteins indicated that they are homologous to known bacterial chitinases.…”
mentioning
confidence: 99%
“…Several studies on the isolation and preparation of antifungal enzyme chitinase from microorganisms and plants have been investigated (Broekaert et al, 1988;Leah et al, 1991;Lorito et al, 1993). But the effect of antifungal enzymes from plants are found to be more potent in inhibition of growth of fungi than those from microorganisms (Roberts and Selitrennikoff, 1988;Park et al, 1992). The present work has been directed towards the selection of suitable, available and inexpensive source for production of chitinase with high activity from a variety of Egyptian higher plant tissues.…”
Section: Introductionmentioning
confidence: 99%